2006
DOI: 10.1523/jneurosci.3139-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Rewards of Nicotine: Regulation by Tissue Plasminogen Activator–Plasmin System through Protease Activated Receptor-1

Abstract: Nicotine, a primary component of tobacco, is one of the most abused drugs worldwide. Approximately four million people die each year because of diseases associated with tobacco smoking. Mesolimbic dopaminergic neurons mediate the rewarding effects of abused drugs, including nicotine. Here we show that the tissue plasminogen activator (tPA)-plasmin system regulates nicotine-induced reward and dopamine release by activating protease activated receptor-1 (PAR1). In vivo microdialysis revealed that microinjection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 47 publications
(57 reference statements)
3
78
1
Order By: Relevance
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have shown that the plasmin system releases dopamine in the NAc upon psychostimulants, which activates long-term synaptic plasticity and remodeling, and acutely participates in the rewarding effects of drugs such as methamphetamine or morphine [13,14,16,17,69]. It has been shown that tPA regulates nicotine-induced reward and dopamine release through protease activated receptor-1 [70]. Using the morphine self-administration procedure, the same group described very recently that tPA deficient mice display more morphine intake in a dose-dependent manner as compared to their wild type littermates [71].…”
Section: Discussionmentioning
confidence: 99%
“…tPA has been shown to regulate morphine-and nicotine-induced DA release in the NAc and is required for morphine and nicotine reward and sensitization (12)(13)(14). Deletion or overexpression of tPA alters methamphetamine-induced place preference and sensitization (13,15).…”
mentioning
confidence: 99%